ESTIMATE PARAMETERS AND RELIABILITY FUNCTION FOR TRUNCATED LOGISTIC DISTRIBUTION: SIMULATION STUDY - Salih, Makki Akram Muhamed; Taqi, Ahmed Yassin (MAGISTRA, 2015)
Abstract : We study In this search the two parameters truncated logistic distribution , and we derived · Probability density function (p.d.f) · Cumulative distribution function (c.d.f) · Reliability function R(x) · Hazard function h(x) For truncated logistic distribution with estimate two parameters and reliability function by Weighted least square method and Maximum likelihood method. Keywords: Logistic Distribution, Truncation Logistic Distribution